Social Enterprise and Creation of Social Value Chain - Erne Suzila Kassim; Md. Mamun Habib (International Journal of Supply Chain Management, 2020)
The main aims of the study are twofold. First is to understand how social enterprises create social values, and second is to evaluate how the values further grow and create other positive social impacts. While a large number of studies on social enterprise has been conducted to assess the benefits to the society, how the benefits create a spill over effect is yet to be well researched. Hence, there are limitations on linking social enterprise to sustainable development. Given the nature of the study context was exploratory, the study was conducted using the qualitative method, with the focus on six cases of social enterprises in Malaysia. The data was analysed using the constant comparison approach and thematic analysis. The analyses suggest two main findings. One is how the strategies of the business model is imperative in creating the values, which are the management, process, product and service, and marketing. Two is the creation of social values, and their chains. These social values are the creation of partnership inter-innovations, which foster for sharing economy, and further enhance social inclusion and finally cultivate social empowerment through shared ownership, financial independence, self-sustainable and strategic alliance. As the world is facing complex social and economic issues, we suggest social enterprise as an agenda for creating a sustainable public wealth. Research implications and future research are discussed.